Amnesty's theory and practice study on income and political effectiveness - Nisrochah Djazuli; Nur Laili Azizah; Revida Alfi Renata; Nindya Gisa Putri; Monna Fadhilah Shidqiyah; Amri Amrulloh (Inovasi Analisis Data, 2024)
Purpose – This research explores the effectiveness of the tax amnesty policy in Indonesia by assessing its effect on tax revenue, taxpayer compliance and administrative efficiency.Design/methodology/approach – A qualitative descriptive approach using in-depth interviews with tax administrators, policy experts with knowledge, experience and/or understanding of the tax amnesty scheme, and taxpayers participating in the tax amnesty scheme, with research and policy implications.Findings – The findings suggest that tax amnesty programs will yield additional revenues in the very short term, but their success also hinges on effective enforcement mechanisms, the legal environment and informing the taxpayer. Concerns over legal uncertainty and perceived inequities resulted in mixed compliance outcomes, articulated by many taxpayers. This study indicates potential for improved voluntary compliance within tax amnesty framework through the use of AI-led tax monitoring, blockchain-enabled compliance verification, and tough post-amnesty deterrence mechanisms.Originality/value – This research provides such a comprehensive assessment of tax amnesty policies in a developing economy context and novel policy suggestions derived from its findings. The study provides a solution-oriented trajectory for tax compliance and administrative efficiency within the context of digital transformation and regulatory reforms.Research Implications – It is recommended that policymakers avoid black-box thinking and rather pursue a balanced range of measures such as tax incentives, legal certainty, and digital monitoring channels so that tax amnesty programs can ultimately serve the objective of revenue sustainability and long-term compliance.